1995
DOI: 10.1159/000188737
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cytokine Levels in Hemolytic Uremic Syndrome

Abstract: The cytokines tumor necrosis factor-α (TNF-α) and its soluble TNF receptors 55 and 75 (sTNFR55, sTNFR75), interleukin-1β (IL-1β) and interleukin-6 (IL·6) were measured in plasma from 13 patients with the hemolytic uremic syndrome (HUS) on admission. No significant changes in the plasma levels of TNF-α and IL-1β were detected in the HUS patients as compared to the plasma levels of the control groups. Levels of IL-6 were significantly elevated in the plasma of those HUS patients who had extrarenal manifestations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 22 publications
2
46
0
1
Order By: Relevance
“…Inward et al [14] reported that two of 19 children with VT-producing E. coli infection complicated with HUS were positive for serum TNF-á. Furthermore, van de Kar et al [15] showed no increase in plasma TNF-á in HUS patients compared to healthy controls, and Fitzpatrick et al [16] found TNF-á present in the plasma of only one of 16 patients with HUS. The data on serum cytokines in mice from the present study were largely consistent with these clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…Inward et al [14] reported that two of 19 children with VT-producing E. coli infection complicated with HUS were positive for serum TNF-á. Furthermore, van de Kar et al [15] showed no increase in plasma TNF-á in HUS patients compared to healthy controls, and Fitzpatrick et al [16] found TNF-á present in the plasma of only one of 16 patients with HUS. The data on serum cytokines in mice from the present study were largely consistent with these clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…Because it was reported that LPS and inflammatory cytokines induced Gb3/CD77 expression on some endothelial cells (19), it may be possible that they potentiate VT cytopathology (30). However, the effects of LPS on VT toxicity depend on when it is administered (31).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, infection, injury and/or isquemia results in the release of pro-inflammatory mediators, and this response is then downregulated by the release of anti-inflammatory mediators, re-127 PMN FUNTIONALITY AND SEVERITY IN HUS sulting in the restoration of homeostasis. In fact, HUS patients consistently showed increased levels of anti-inflammatory cytokines, which have been associated with a more severe renal dysfunction of patients (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%